WHO Expert Committee on Biological Standardization : thirty-seventh report, meeting held in Geneva from 1 to 8 December 1986 - WHO Expert Committee on Biological Standardization; World Health Organization (Geneva : World Health Organization, 1987)
Announces changes in the status or development of international standards for 35 biologicals, classified as antibiotics, antibodies, antigens, blood products and related substances, endocrinological and related substances, and a miscellaneous group of substances. The report also provides detailed information on requirements for the manufacturing, testing, and quality control of selected vaccines, including hepatitis B vaccines made by recombinant DNA techniques in yeast, live mumps vaccine, and inactivated rabies vaccine produced in continuous cell lines. Of particular practical interest is an extensive report on a WHO meeting concerned with the use of recombinant DNA techniques to produce hepatitis B vaccines. The report also includes amendments to previous requirements for oral poliomyelitis vaccine and for diphtheria toxoid, pertussis vaccine, tetanus toxoid, and combined vaccines.
General -- Substances: Antibiotics -- Antibodies -- Blood products and related substances -- Endocrinological and related substances -- Miscellaneous -- requirements for biological substances -- Annaxes
Keywords: Biological Products; Pharmacology, Toxicology and Clinical Technology